Chronic Stress Effects on Hippocampal Structure and Synaptic Function: Relevance for Depression and Normalization by Anti-Glucocorticoid Treatment - Krugers, Harmen J.; Lucassen, Paul; Karst, Henk; Joels, Marian (Frontiers in Synaptic Neuroscience, 2010)
Exposure of an organism to environmental challenges activates two hormonal systems that help the organism to adapt. As part of this adaptational process, brain processes are changed such that appropriate behavioral strategies are selected that allow optimal performance at the short term, while relevant information is stored for the future. Over the past years it has become evident that chronic uncontrollable and unpredictable stress also exerts profound effects on structure and function of limbic neurons, but the impact of chronic stress is not a mere accumulation of repeated episodes of acute stress exposure. Dendritic trees are reduced in some regions but expanded in others, and cells are generally exposed to a higher calcium load upon depolarization. Synaptic strengthening is largely impaired. Neurotransmitter responses are also changed, e.g. responses to serotonin. We here discuss: a) the main cellular effects after chronic stress with emphasis on the hippocampus, b) how such effects could contribute to the development of psychopathology in genetically vulnerable individuals, and c) their normalization by brief treatment with anti-glucocorticoids.